The impact of partisan politics on the decision making processes of local councils: a case study of Kwekwe City Council. (2000 – 2017) - Muchara, Brenda K. (Midlands State University, 2018)
Worldwide, public administration has been considered to be the most crucial aspect in the field of administration where all administrative duties are supposed to be performed in order to serve the interest of the general mass. Local authorities perform their duties as a sub division of the central government and decision making at local council should be exercised as an independent action which should not be influenced by partisanship nor do central government meddle in the decision making processes of local council. With the dawn of independence in Zimbabwe the citizens had a vision of better and effective decision making process at municipals as decision were now going to be made by their fellow entrusted councilors. The rise of multi-party system in Zimbabwe negatively impacted on the decision making process of local authorities as decision were now being affected by party politics. It was a case study of Kwekwe City Council and the researcher developed a keen interest to research on the topic because partisan politics has brought about many challenges in decision making processes. This impact that is posed by partisan politics in local authorities is that decisions that are being made at the council are those mainly supported by the party which has the majority seats in the council chamber and some of the decisions are not made with the zeal to better the service but as those that serve the interest of the ruling party. Kwekwe City Council has experienced challenges which include inter departmental conflicts, unfair distribution of resource in different wards and promotion and recruitment based on political affiliation. The researcher took a qualitative approach to analyze the impact of partisan politics on the decision making processes of local authorities. Questionnaires, observations, interviews and document analysis were used as methods of data gathering. Thematic and content analysis were the methods that were used by the researcher to analyze the data gathered. The researcher during data collection made sure that ethical considerations were taken into account. The researcher from the data one gathered concluded of the fact that partisan politics in local authorities has caused a lot of challenges to the decision making processes of council and many decisions that are being made at council are not motivated by the zeal for a better service delivery but are done to serve the interest of political parties.